Model Kinerja Pegawai: Kepemimpinan, Budaya Kerja, dan Motivasi Kerja dengan Kepuasan kerja variabel intervening - Gusni Ami Jayanti; Nazwirman Nazwirman (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
The research aims to analyze and describe the influence of Leadership Variables, Work Culture, Work Motivation, Job Satisfaction towards Job Satisfaction Variables and Performance Variables on the Investment Alert Task Force of the Financial Services Authority. A total of 100 samples were analyzed using SEM (Structural Equation Model) with SmartPLS software. The results showed that leadership had a significant positive direct effect on job satisfaction. Leadership has a significant positive effect on performance. Work Culture has a significant positive effect on Job Satisfaction. Work Culture has a significant positive effect on performance. Work motivation has a significant positive effect on job satisfaction. Work motivation has a significant positive effect on performance. Job satisfaction has a significant positive effect on the performance of the Investment Alert Task Force. Job Satisfaction is able to mediate on Leadership on Performance. Job Satisfaction is able to mediate the Work Culture of Performance. Job Satisfaction is able to mediate on Work Motivation on Performance. Efforts to improve the performance of the Investment Alert Task Force employees of the financial services authority need to consider the four variables that influence it.